Design treatments for Iraqi kitchen spaces (comparative study) (Journal of the College of Basic Education, 2022)
The treatment design of the interior space for the Iraqi kitchens is the importance maitance which has to know from every designer. That depends an his knowledge and how he has to apply this staff in the whole new valid kitchen which developed rapidly in this field of the interior design. This treatment gives to the designers more solution and varied variables to comprise his knowledge with the real life; which are both of them are virgin. So the research discuss in the first chapter the problem of the research , which appeared in the luck of the most Iraqi kitchens for the important and easily done in home work jobs ; and to stand by of the strong and weakness of the ways to how to treat the element which the kitchens contains ; and the importance of the treatment of the suitable work comparing that with the global criteria in the art 0f the interior design which contain the skills and values of the beautiful and job analysis factors . For these issues the searcher discusses in the second chapter the different treatment and the kinds of movement which has done in the Iraqi kitchens. beside that the kinds of the basic and kinds of the interior design in order to select one of them to every kitchen in every house here and every where in the global . In condition to have the space in good area and the global criteria in ventilation ; the lighting ; colures; and the row materials used in the kitchens . In chapter three the searcher appeared the practice and applied of three Iraqi kitchens as a sample of this research ;comparing that with the view of the literature that she derived and reached many of the results and conclusion ; the importance which has to infusive on the tingle of the interior design of the kitchens are contain these option : ( cooker , refrigerator , sink ) beside that a good environmental an suitable ventilation ; lighting and easily movement in kitchens area space for the house wife's.